Nicotinamide phosphoribosyltransferase (NAMPT/PBEF/visfatin) is a tumoural cytokine released from melanoma. (November 2015) - Grolla, Ambra A.; Torretta, Simone; Gnemmi, Ilaria; Amoruso, Angela; Orsomando, Giuseppe; Gatti, Marco; Caldarelli, Antonio; Lim, Dmitry; Penengo, Lorenza; Brunelleschi, Sandra; Genazzani, Armando A.; Travelli, Cristina
Summary High plasma levels of nicotinamide phosphoribosyltransferase (NAMPT), traditionally considered an intracellular enzyme with a key role in NAD synthesis, have been reported in several oncological, inflammatory and metabolic diseases. We now show that eNAMPT can be actively released by melanoma cells in vitro. We analysed the mechanisms of its release, and we found both classical and non‐classical pathway involvement. eNAMPT released by melanoma cells, in our hands, has paracrine and autocrine effects: it activates MAPK, AKT and NF‐κB pathways and increases colony formation in anchorage‐independent conditions. eNAMPT also induces M1 polarization in human monocytes. Last, we demonstrate, for the first time in any cancer type, that eNAMPT levels in plasma of tumour‐bearing mice increase and that this increase can be reconducted to the tumour itself. This provides an important cue on previous observations that eNAMPT is increased in patients with cancer. Moreover, silencing NAMPT in melanoma cells leads to a reduction in the tumour growth rate. Our findings extend the basis to consider eNAMPT as a cytokine involved in tumour progression.